Palliative care in pediatric Leukemia: The value added to care - Manjusha Nair (Pediatric Hematology Oncology Journal, 2025)
Childhood leukemias are one of the most curable cancers, because of revolutionary developments in the field of pediatric oncology. The diagnosis of leukemia in a child impacts the whole family, with disruption in their routines, behavior, attitudes and relationships, with long-term adverse psychosocial consequences. Comprehensive treatment of cancer involves not only the management of physical symptoms due to cancer but also attention to psychological, socio-cultural and spiritual domains of the child and family as a unit. Pediatric palliative care offers a holistic approach towards supporting the children and families during the entire course of treatment regardless of prognosis, and includes the full spectrum of physical, psychological, social, and spiritual care. Palliative care should go along with active cancer treatment and should be smoothly introduced to patients and their families, so that they do not feel abandoned by their treating teams if curative treatment is unsuccessful and palliative care teams are abruptly involved. Recent evidence proves that integration of palliative care is associated with significant improvements in the quality of life of children affected with cancer and their families, and should begin at diagnosis itself. This review explores the various ways in which palliative care can be incorporated in the treatment of children with haematological malignancies.